Method of producing metal

JP2025036431APending Publication Date: 2025-03-14METALYSIS
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024207822
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2015-03-10
Filing Date
2024-11-28
Publication Date
2025-03-14

Smart Images

  • Figure 2025036431000001_ABST
    Figure 2025036431000001_ABST
Patent Text Reader

Abstract

To provide: a method of producing a non-metallic feedstock powder; the non-metallic feedstock powder; and a method for producing metal alloy.SOLUTION: A method of producing a non-metallic feedstock powder suitable for reduction to metal comprises the steps of: combining a liquid with solid metal oxide particles to form a mixture; subjecting the mixture to high-shear mixing to form a liquid suspension of metal oxide and the liquid; and drying the liquid suspension by using a fluidized-bed spray-granulation process to grow a plurality particles to form the non-metallic feedstock powder. The method allows feedstock powders to be grown to desired particle sizes. The method allows production of feedstock powders having controlled compositions.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method of producing a feedstock powder for reduction to a metal, a feedstock powder, and a method of producing a metal by reduction of a feedstock powder. The present invention may be particularly advantageous for producing metal alloys, such as metal alloy powders or intermetallic powders. [Background technology]

[0002] The present invention relates to a method of forming a feedstock powder and a method of forming a metal by reducing the feedstock powder to form a metal.

[0003] In recent years, there has been great interest in the direct production of metals by the direct reduction of solid feedstocks, e.g., metal oxide feedstocks. One such direct reduction process is the Cambridge FFC® electrolysis process (described in US Pat. No. 5,399,633). In the FFC process, a solid compound, e.g., a metal oxide, is placed in contact with a cathode in an electrolysis cell containing a molten salt. An electrical potential is applied between the cathode and anode of the cell such that the compound is reduced. In the FFC process, the electrical potential to produce the solid compound is lower than the deposition potential of the cations from the molten salt.

[0004] Other reduction processes have also been proposed for reducing feedstock in the form of solid non-metallic compounds connected to a cathode, such as the polar™ process described in US Patent No. 5,399,623 and the process described in US Patent No. 5,399,623. Non-metallic compounds such as metal oxides can also be directly reduced by metallothermal processes, for example the molten salt calcium process described in US Patent No. 5,399,623.

[0005] Conventional practice of the FFC process and other solid electrolytic reduction processes typically involves the production of a feedstock in the form of a porous preform or precursor, which is made from a sintered powder of the solid non-metallic compound to be reduced. This porous preform is then carefully coupled to a cathode to allow the reduction to occur. Once several preforms are coupled to the cathode, the cathode can be placed in a molten salt to reduce the preforms.

[0006] US Patent No. 5,993,366 discloses a method for producing metal powders, comprising placing a volume of a feedstock containing a plurality of non-metallic particles in an electrolytic cell and applying an electrical potential between a cathode and an anode to reduce the feedstock to metal powder. The feedstock powder in US Patent No. 5,993,366 is disclosed as non-metallic particles derived from crushed rock or mineral, or natural sand. Typically, the feedstock powder must be screened, e.g., sieved, to select a portion of the non-metallic particles having a desired average particle size or a desired particle size distribution.

[0007] There are several disclosures that metal alloys can be produced by direct reduction of preforms containing two or more different metal oxides. For example, US Pat. No. 5,399,633 discloses the production of titanium aluminum alloys by reduction of preforms containing both titanium oxide and aluminum oxide. However, it can be difficult to prepare preforms with the appropriate stoichiometry in a narrow range to produce the desired alloy. This can be due in part to the size of some of the oxide particles, or due to the disparity in particle size between oxide particles of some different compositions. For example, titanium dioxide powder is usually supplied as a fine powder with a small average particle size, typically in the range of 1-2 micrometers. On the other hand, alumina powder is typically available in much larger average particle sizes, for example in the range of 8-10 micrometers. Other less common metal oxides, such as vanadium oxide, may only be commercially available in very large particle sizes, for example with an average particle size of about 100 micrometers. This disparity in particle size means that it is difficult to uniformly distribute the alloying elements in the preform to form the metal alloy.

[0008] This problem becomes acute when it is desired to produce alloy powders. For example, it may be particularly desirable to produce metal alloy powders with average particle sizes in the range of 100 to 250 micrometers, or even smaller than 100 micrometers. It is difficult to produce, for example, Ti-6Al-4V alloy powders with this desired particle size by reducing a feedstock powder formed by simple agglomeration of titanium oxide, aluminum oxide, and vanadium oxide particles. This is due to the large particle size of the vanadium oxide particles (approximately 100 micrometers) and the fact that vanadium should only account for 4% by weight of the resulting Ti-6Al-4V alloy powder.

[0009] Mixed oxide preforms can be obtained by mixing different metal oxide powders with a solvent and performing a ball milling procedure. After ball milling, the solvent can be evaporated and the remaining powder can be compressed to form a preform. However, ball milling is a relatively gentle process and preforms produced in this manner are not homogeneous and do not have a controlled narrow range of stoichiometry. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] WO99 / 64638 [Patent Document 2] WO03 / 076690 [Patent Document 3] WO03 / 048399 [Patent Document 4] EP1445350 [Patent Document 5] WO2013 / 050772 Summary of the Invention [Means for solving the problem]

[0011] The present invention provides a method for producing a non-metallic feedstock powder, a non-metallic feedstock powder, and a method for forming a metal by reduction of a non-metallic feedstock powder, as defined in the accompanying independent claims, to which reference is now made. Preferred or advantageous features of the invention are set out in the various dependent claims.

[0012] Thus, a method of producing a non-metallic feedstock powder suitable for reduction to a metal may include combining a liquid with solid metal oxide particles to form a mixture, subjecting the mixture to high shear mixing to form a suspension of the metal oxide and liquid, and drying the suspension using a fluidized bed spray granulation process to grow a plurality of particles and form the non-metallic feedstock powder. The spray granulation process grows the plurality of feedstock particles layer by layer to a predetermined average particle size.

[0013] The liquid that is mixed with the metal oxide particles to form the mixture may advantageously comprise an aqueous solution of water and an organic binder, such as polyvinyl alcohol (PVA). Many other suitable binders are known. For example, suitable binders may include polyvinylpyrrolidone (PVP) or hydroxyethyl cellulose (HEC). By subjecting the mixture of the liquid and the metal oxide particles to a high shear mixing process, the metal oxide particles can be ground to a similar fineness, regardless of any large variations in particle size that may exist before the high shear mixing. That is, if the metal oxide particles that are mixed with the liquid to form the mixture have a wide particle size distribution, the high shear mixing process can advantageously reduce the overall average particle size and grind the particles to a narrow overall particle size distribution. By forming a suspension containing uniformly distributed metal oxide particulates, it is advantageously possible to use a spray granulation process to grow the particles to a predetermined average particle size for forming the feedstock powder.

[0014] The ratio of liquid to metal oxide powder in the mixture can vary. However, it is preferred that the mixture is between 50% and 70% by weight metal oxide, with the remainder being liquid. At oxide loadings above 70% by weight, it may be difficult to create high shear mixing sufficient to form a homogenized suspension. Suspensions formed at loadings above 70% are difficult to pump into the spray granulator. At oxide loadings below 50% by weight, it may take too long to build up the feed particles. At lower oxide loadings, the particles produced may be more spherical. Therefore, it may be advantageous to maintain the oxide loading between 50% and 60% by weight of the mixture, or between 50% and 55% by weight of the mixture.

[0015] The step of drying the suspension may include spraying a portion of the suspension into a heating chamber of a fluidized bed spray granulator, thereby removing liquid from individual droplets of the suspension to form a plurality of seed particles, maintaining the plurality of seed particles in the heating chamber by a fluidizing gas flow, and spraying a further portion of the suspension into the heating chamber, such that the droplets of the suspension successively adsorb onto the plurality of seed particles and dry thereon, thereby allowing the plurality of feedstock particles to grow incrementally to a predetermined particle size.

[0016] Fluid bed spray granulation processes are known and have particular application in the pharmaceutical industry. As the feed liquid is sprayed into the chamber, it dries to form seed or seed particles. The seed particles are maintained inside by the fluidizing gas flow. As more feed liquid is sprayed into the chamber, it deposits a layer on the seed particles. The seed particles grow larger and form an onion-like structure. Substantially spherical particles are formed. The particles grow until they are too large to be maintained within the fluidizing gas flow and then fall out of the bottom of the heated chamber. The resulting particles are dry, substantially spherical, and dust-free.

[0017] Process parameters that can be controlled include the fluidization air velocity and air temperature (inlet temperature). For purposes of this invention, the airflow during spray granulation is approximately 100 m per hour. 3 190m from 3 Preferably 130m per hour 3 170m from 3 For the purposes of the present invention, it may be suitable for the air temperature to be between 120°C and 190°C, preferably between 130°C and 150°C.

[0018] Control of the process parameters allows the production of granules with a defined average particle size in the range of about 10 micrometers to about 10 millimeters. Different parameters may need to be selected to form particles of the same size with oxides of different densities. Such a high degree of control of the process allows the final particle size and particle size distribution to be controlled within very precise tolerances. Furthermore, the process yield can be substantially greater than 90%. For example, when the process is carried out continuously, yields of greater than 95% or 98% are achievable.

[0019] Controlling the average particle size may allow the formation of non-metallic feed powders of specific particle sizes to produce metal powders with specific powder characteristics. WO2014 / 068267 describes the production of metal powders with specific powder characteristics for use in specific powder metallurgy processes.

[0020] The suitable particle size range of the metal powder after reduction of the feedstock may vary depending on the desired end use of the metal powder. For example, the following provides an indication of ranges that are typically suitable for various powder metallurgy processes. In each case, the lower value of the range represents the D10 particle size and the higher value of the range represents the D90 particle size.

[0021] Metal Injection Molding (MIM) - Particle size range between 5 microns to 30 microns. Gas Dynamic Cold Spray (GDCS)- Particle size range between 15 microns to 45 microns. Selective Laser Melting (SLM) - Particle size range between 20 microns to 50 microns. Electron Beam Melting (EBM) - Grain size range between 50 microns to 100 microns. Laser Metal Deposition (LMD) - Particle size range between 50 microns to 125 microns. Cold Isostatic Pressing (CIP) - Particle size range between 45 microns to 150 microns. Hot Isostatic Pressing (HIP) - Grain size range between 45 microns to 200 microns.

[0022] The actual particle size ranges of powders for use in any of the above identified processes may vary outside of the ranges set forth above, these values ​​are provided as a guide to preferred or ideal particle size ranges for metal powders used in these processes.

[0023] An advantage of the spray granulation process is that it allows for the formation of substantially spherical feedstock particles. A powder formed from a plurality of such particles can be reduced to a metal powder of substantially spherical metal particles. The substantially spherical particles are rounded, without angular edges, and have a low aspect ratio between the x-, y-, and z-axes. This aspect ratio is approximately 1:1:1. Spherical metal powder particles are advantageous in many powder processing techniques. Currently, spherical metal powders are only produced by processes such as atomization or spheronization of metal particles. The feedstock powders disclosed herein can advantageously be directly reduced to produce a metal powder consisting of a plurality of substantially spherical metal powder particles.

[0024] The method may be particularly advantageous in forming alloys and alloy powders. For purposes of this application, intermetallic compounds are considered alloys. Thus, a first set of metal oxide particles and a second set of metal oxide particles may be combined with a liquid to form a mixture. The first set of metal oxide particles has a different composition than the second set of metal oxide particles. Preferably, the first set of metal oxide particles includes a first metal oxide and the second set of metal oxide particles includes a second metal oxide, the first metal being a different metal than the second metal. High shear mixing of the mixture may grind the different sets of metal oxide particles to a fine particle size, for example, an average particle size of less than 2 micrometers. The suspension formed by the high shear process includes metal oxides of uniform fineness. Furthermore, each of the different metal oxides is uniformly distributed. Controlling the ratio of the first set of metal oxide particles to the second set of metal oxide particles may allow for control of the stoichiometry of the feedstock powder formed using the method. The different metal oxide particles can be uniformly distributed in the produced feedstock powder, allowing a narrow range of stoichiometry to be achieved.

[0025] Advantageously, the process can be applied to particles in which the first and second sets of metal oxide particles have substantially different average particle sizes. The first and second sets of metal oxide particles may have average particle sizes that differ by more than a factor of two. For example, the first and second sets of metal oxide particles may have an average particle size of 5 micrometers, and the second set of metal oxide particles may have an average particle size of 10 micrometers. The first and second sets of metal oxide particles may have average particle sizes that differ by more than a factor of 10. The first and second sets of metal oxide particles may have average particle sizes that differ by more than a factor of 100. Whenever there is a large disparity in particle sizes between two or more sets of mixed particles, it is difficult to produce a feedstock with a substantially uniform particle size without losing a significant amount of material. The same problem occurs when one set of particles has a wide particle size distribution. The proposed process addresses these issues and allows for the controllable formation of feedstock powders consisting of powder particles of substantially uniform size.

[0026] Feedstock powders containing complex metal oxide compositions can be produced by mixing more than two sets of different metal oxide particles and processing them as described above. For example, the method of producing a feedstock powder may include mixing three or more sets of metal oxide particles, each having a different composition. It may be desirable to form a mixture that includes a liquid, a set of titanium dioxide particles having an average particle size of less than 2 micrometers, a set of alumina particles having an average particle size of about 8 micrometers, and a vanadium pentoxide powder having an average particle size of about 100 micrometers. Advantageously, the method disclosed herein may allow the formation of a feedstock containing substantially spherical particles with a uniform distribution of each of these three oxides. Such a feedstock can be used to form a titanium-aluminum-vanadium alloy.

[0027] It may be advantageous for the metal oxide particles that are mixed with the liquid to form the mixture to be synthetic or purified metal oxide particles. Such particles are typically agglomerates of very fine particles. For example, vanadium oxide powder particles having a diameter of 100 micrometers may be agglomerates of very fine subparticles having a particle size of, for example, less than 1 micrometer. Such particles can be efficiently pulverized using high shear mixing processes.

[0028] The feed powder is preferably grown to a predetermined average particle size. The predetermined average particle size of the feed powder may be anywhere in the range of 10 micrometers to 10 millimeters. A preferred range may be between 50 micrometers and 5 millimeters, for example between 50 micrometers and 200 micrometers. Advantageously, the process for forming the feed powder may be controlled such that the feed powder has a narrow particle size distribution. For example, the width of the particle size distribution may be less than 100 micrometers between the D10 and D90 diameters. For example, the particle size distribution may be 50 micrometers or less.

[0029] The average particle size or average particle size can be determined by several different techniques. For example, the average particle size (average particle size) can be determined by sieving, laser diffraction, dynamic light scattering, or image analysis. The exact value of the average particle size of powder particles may vary slightly depending on the measurement method used to determine the average value, but in practice, this value will be similar if the particles do not have an excessively high aspect ratio. For example, a person skilled in the art will understand that the average particle size of the same powder may be indicated as 150 micrometers when analyzed by sieving, for example, and 142 micrometers when analyzed by a different technique, such as laser diffraction. A preferred technique for determining the average particle size is laser diffraction. For example, the average particle size can be determined using an analyzer such as a Malvern Mastersizer Hydro 2000 MU. Such analyzers can also be used to determine the particle size range or particle size distribution.

[0030] One standard way to determine the particle size distribution in a powder is to refer to the D10 and D90 values. D10 is the particle size value below which 10% of the particle population falls. D90 is the particle size value below which 90% of the particle population falls. Feedstock powders with a broad particle size distribution will have a large difference between the D10 and D90 values. Similarly, feedstock powders with a narrow particle size distribution will have a small difference between the D10 and D90 values.

[0031] The high shear mixing step can be preferably carried out in a high shear mixer having a rotor capable of rotating at more than 5000 rpm, for example more than 6000 rpm, or about 6500 rpm. The rotor rotates relative to a stator in a vessel containing the mixture. That is, the rotor and stator are in a vessel containing the mixture of liquid and metal oxide particles. The difference in velocity between the liquid near the tip of the rotor and the liquid adjacent to the stator creates a zone of extremely high shear in the liquid. This high shear breaks up the metal oxide particles in the liquid and forms a suspension of the metal oxide and liquid.

[0032] A variety of high shear mixers are readily available on the market. For example, small quantities can be processed by high shear mixing using an IKA G45 M dispersion mixer.

[0033] Preferably, the dried particles obtained from the spray granulator are heat treated before reduction to metal. Heat treatment by a suitable calcination process can remove any traces of organic binder remaining on the individual particles. The absence of organic binder can provide some porosity to the particles, which can be particularly advantageous in some methods of reducing particles to metal, such as electrolytic reduction methods using molten salts. For example, the feed powder can include a plurality of particles with a porosity between 5% and 50%, such as between 10% and 30%. In other words, the individual particles can have a porosity between 5% and 50%. Heat treatment can also impart some mechanical strength to each particle.

[0034] To produce homogenized mixed metal oxide particles, it may be advantageous to heat treat, i.e., calcinate, the particles at a relatively high temperature. Thus, the metal oxide particles of the feedstock powder may be homogenized mixed metal oxide particles, each having both a predetermined particle size and a predetermined stoichiometric amount of metal elements. The feedstock powder may then be reduced to form a homogenized metal alloy having a predetermined alloy composition. Thus, it may be desirable to heat treat the feedstock particles at a temperature above 900°C, for example, between about 1000°C and 1400°C.

[0035] A method of producing a metal may include forming a non-metallic feedstock using a method described herein and reducing the non-metallic feedstock powder to form a metal. The feedstock powder may be reduced directly as a powder to a metal or may be formed into a preform for subsequent reduction. Preferably, the feedstock powder is reduced directly as a powder to form a metal powder. The feedstock powder may be reduced by any suitable method, for example by metallothermic reduction.

[0036] It may be preferred to reduce the feed powder by electrolytic reduction of the feed powder in contact with a molten salt. For example, a volume of the feed powder may be placed in an electrolytic cell containing molten salt, and a potential may be applied between the anode and cathode to reduce the feed to metal. It may be particularly preferred to carry out the reduction of the feed powder using an FFC process in which the feed powder is contacted with a cathode and molten salt in an electrolytic cell, and a potential is applied between the cathode and anode such that the feed is reduced.

[0037] A method of producing metal powder may include positioning a cathode and an anode in an electrolytic cell in contact with a molten salt, such that a top surface of the cathode supports a volume of a non-metallic feedstock and a bottom surface of the anode is vertically spaced apart from the feedstock and the cathode, and applying an electric potential between the cathode and the anode such that the feedstock is reduced to a plurality of discrete metal particles.

[0038] Some reduction processes can only work if the molten salt or electrolyte used in the process contains metal species (reactant metals) that form more stable oxides than the metal oxide or compound being reduced. Such information is readily available in the form of thermodynamic data, specifically Gibbs free energy data, and can conveniently be determined from standard Ellingham diagrams, or dominance diagrams, or Gibbs free energy diagrams. Thermodynamic data and Ellingham diagrams regarding oxide stability are available to and understood by electrochemists and extractive metallurgists (those skilled in the art in this case are well aware of such data and information).

[0039] Thus, a suitable electrolyte for the electrolytic reduction process may include a calcium salt. Calcium forms more stable oxides than most other metals and may therefore act to promote the reduction of any metal oxide that is less stable than calcium oxide. In other cases, salts containing other reactive metals may be used. For example, the reduction process according to any aspect of the invention described herein may be carried out using salts containing lithium, sodium, potassium, rubidium, cesium, magnesium, calcium, strontium, barium, or yttrium. Chlorides or other salts may also be used, including mixtures of chlorides or other salts.

[0040] By selecting the appropriate electrolyte, almost any metal oxide particle can be reduced using the method and apparatus described herein. Natural minerals containing one or more of such oxides can also be reduced. In particular, the oxides of beryllium, boron, magnesium, aluminum, silicon, scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, germanium, yttrium, zirconium, niobium, molybdenum, hafnium, tantalum, tungsten, and lanthanides (including lanthanum, cerium, praseodymium, neodymium, samarium) can be reduced using molten salt, preferably containing calcium chloride.

[0041] One of ordinary skill in the art can select an appropriate electrolyte for reducing a particular metal oxide, and in most cases an electrolyte containing calcium chloride will be suitable.

[0042] In a particularly advantageous embodiment, the metal produced is a titanium-aluminium-vanadium alloy. Titanium oxide, aluminium oxide and vanadium oxide particles may be mixed with a liquid in appropriate ratios to form a mixture which is then subjected to high shear mixing to form a homogeneous suspension of the different metal oxides in the liquid. Reduction of the feedstock powder thus formed is a titanium-aluminium-vanadium alloy of a predetermined composition.

[0043] A feedstock powder suitable for reduction to metal may also be provided. The feedstock powder may include a plurality of feedstock particles having a predetermined average particle size. Suitably, the feedstock powder comprises substantially spherical particles. The feedstock powder is formed by the process described above. The feedstock powder may have an average particle size between 50 micrometers and 500 micrometers, for example between 100 micrometers and 250 micrometers.

[0044] In one embodiment, the feed powder may include titanium oxide and at least one additional metal oxide. The at least one additional metal oxide may be aluminum oxide, and / or vanadium oxide, and / or niobium oxide, and / or chromium oxide. The titanium alloy powder formed may have a composition at or near the composition of Ti-6Al-4V. The titanium alloy powder formed may have a composition at or near the composition of Ti-6Al-6V-2Sn.

[0045] In one embodiment, the feed powder may include tantalum oxide and at least one additional metal oxide, which may be aluminum oxide, and / or tungsten oxide, and / or titanium oxide.

[0046] The step of drying the suspension may further include spraying a portion of the suspension into a heating chamber of a fluidized bed spray granulation apparatus, thereby removing liquid from individual droplets of the suspension to form a plurality of seed particles; maintaining the plurality of seed particles in the heating chamber by a fluidizing gas flow; and spraying a further portion of the suspension into the heating chamber, such that the droplets of the suspension successively adsorb onto and dry on the plurality of seed particles, thereby growing a plurality of feedstock particles.

[0047] Any of the additional processing features for forming the feedstock powder disclosed herein above may be combined with this aspect of the feedstock powder invention.

[0048] The feed powder may be suitable for reduction to form a metal alloy, for example a metal alloy powder. Advantageously, each non-metallic particle may be a solid solution mixed oxide. Such oxide may be reduced to form a metal alloy particle with a homogeneous distribution of the metal elements. The feed powder may also be suitable for reduction to a Ti-Al-V alloy, the feed powder comprising titanium, aluminum, vanadium, and oxygen.

[0049] The feed powder may be a homogenized mixed oxide powder. The feed powder may comprise titanium, aluminum, and vanadium along with oxygen, and the proportions of the metal elements in the oxide powder may be between 5.5% and 8% by weight aluminum, between 3.5% and 6% by weight vanadium, and the remainder titanium.

[0050] Depending on the composition, the feed powder may be suitable for reduction to titanium-aluminide alloy powder, or titanium-tantalum alloy powder, or tantalum-tungsten alloy powder, or tantalum-aluminum alloy powder.

[0051] Titanium aluminide (48Ti-48Al-2Nb-2Cr) is a high temperature titanium intermetallic compound used in turbines and specifically in the aerospace industry.

[0052] Titanium-tantalum (70Ti-30Ta) is a biomedical alloy that is used, for example, in dental applications.

[0053] Tantalum tungsten (Ta-2.5W) exhibits excellent corrosion resistance at high temperatures and is used in the chemical industry, for example for piping.

[0054] Tantalum aluminum is a potential capacitor material. This combination results in a higher dielectric constant than tantalum alone, and therefore a higher capacitance. [Brief description of the drawings]

[0055] [Figure 1] FIG. 1 is a schematic diagram illustrating a high shear mixing device suitable for use in embodiments of the present invention. [Diagram 2] FIG. 1 is a schematic diagram illustrating a fluidized bed spray granulation apparatus that can be used in embodiments of the present invention. [Diagram 3] FIG. 1 is a schematic diagram illustrating the formation of feedstock powder particles using a spray granulation process. [Figure 4] 1 is a photomicrograph showing particles of a feedstock powder formed using an embodiment of the present invention. [Diagram 5] 5 is an electron microscope photograph of a portion of the powder of FIG. 4. [Figure 6] FIG. 6 is an energy dispersive X-ray spectroscopy (EDS) elemental map showing the distribution of aluminum over the area shown in the micrograph of FIG. 5. [Figure 7] FIG. 6 is an energy dispersive X-ray spectroscopy (EDS) elemental map showing the distribution of vanadium over the range shown in the micrograph of FIG. 5. [Figure 8] FIG. 6 is an energy dispersive X-ray spectroscopy (EDS) elemental map showing the distribution of titanium over the area shown in the micrograph of FIG. 5. [Figure 9]FIG. 1 is a schematic diagram illustrating an electrolytic apparatus arranged to reduce a feedstock powder according to an embodiment of the present invention. [Figure 10] FIG. 10 is a schematic cross-sectional view showing further details of the cathode structure of the electrolytic device of FIG. [Figure 11] FIG. 11 is a plan view of the cathode shown in FIG. [Figure 12] FIG. 5 is a SEM micrograph of Ti—Al—V alloy powder particles produced by reducing the feedstock powder of FIG. 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0056] Specific embodiments of one or more aspects of the present invention will now be described with reference to the figures.

[0057] The present invention relates to a method of forming a feedstock powder suitable for reduction to a metal. The present invention also relates to a feedstock powder formed by the method, and to a method of producing a metal comprising reducing the feedstock powder formed by the method. The method of forming the feedstock powder comprises combining a liquid with metal oxide particles to form a mixture, preferably having an oxide percentage between 50% and 70% by weight, subjecting the mixture to high shear mixing to form a suspension, and drying the suspension using a fluid bed spray granulation process, which is a process of high shear mixing and fluid bed spray granulation, which will now be generally described.

[0058] FIG. 1 is a schematic diagram of a high shear mixer 10 that may be suitable for forming a suspension in an embodiment of the present invention. The high shear mixer 10 comprises a vessel 11 containing a mixture 12 of liquid and metal oxide particles. A high shear mixer 20 is positioned in contact with the liquid mixture 12. The high shear mixer includes a motor 21, a connecting shaft 22, a rotor 23, and a stator 24. The rotor 23 is separated from the stator 24 by a narrow air gap 25. In use, the motor 21 rotates the rotor 23 at a speed typically between 5000 rpm and 10000 rpm. As the rotor rotates, the stator remains stationary and the velocity difference between the liquid near the rotor and the stator creates high shear in the liquid.

[0059] Typically, the liquid mixture 12 consists of an aqueous solution of a binder, such as polyvinyl alcohol (PVA), and a proportion of metal oxide particles. The high shear forces generated in the liquid mixture 12 cause the metal oxide particles to break up. Various parameters can be altered to affect the final particle size of the broken down oxide. For example, parameters such as the rotational speed of the rotor 23, the distance of the air gap 25 between the rotor and the stator, and the ratio of metal oxide to liquid in the liquid mixture 12, as well as the mixing time, can all be varied to affect the particle size of the metal oxide resulting from the high shear mixing process. The high shear mixing forms a suspension of finely divided metal oxide particles in a liquid, for example an aqueous solution of PVA.

[0060] A range of suitable high shear mixers or batch mixers are known and commercially available. For example, IKA® manufactures a range of batch mixers for forming suspensions of pharmaceuticals. Such high shear mixers may be suitable for use in embodiments of the present invention.

[0061] FIG. 2 is a schematic diagram of a fluidized bed spray granulation apparatus 30. The apparatus includes a heating chamber through which an upward hot air stream 32 passes. A nozzle 33 allows droplets of suspension 34 to be injected into the heating chamber 31. The droplets of suspension 34 may be fed directly from the high shear mixer 10 or transferred to a separate reservoir prior to injection. Upon entering the heating chamber 31, the droplets of suspension 34 dry and form solid particles 35. These solid particles 35 are maintained within the heating chamber 31 by the fluidizing action of the heated air stream 32. As additional droplets of suspension 34 are injected into the heating chamber 31, they adsorb to and dry the existing particles 35, thereby increasing the diameter of the particles 35. As the particles grow, they eventually reach a size that is too large to remain fluidized within the chamber. When the particles reach this diameter, they fall towards the bottom of the chamber and are collected.

[0062] The size, shape, size, and size distribution of the recovered particles 36 can be influenced by controlling parameters such as the oxide loading, injection pressure, and initial droplet size of the suspension, as well as the flow rate of the fluidizing air stream.

[0063] The use of spray granulation technology offers great flexibility in controlling particle size and particle size distribution. By controlling and optimizing the process parameters, particle sizes in the range of 10 micrometers to 10 millimeters can be achieved. This system has the advantage that any particles that are too small that have passed through the spray granulator can be returned to the heating chamber 31 for further growth. Additionally, any particles that are too large can be returned to the high shear mixer. Thus, the process yield should be well above 90%, preferably above 95% or even above 98%.

[0064] FIG. 3 illustrates particle growth in a fluidized bed spray granulator. When droplets of suspension 34 are injected into the heated chamber of the spray granulator, they dry rapidly to form small seed particles 35. As described in connection with FIG. 2, these seed particles 35 are fluidized by a hot air current. Subsequent droplets of suspension 37 adsorb onto the surface of the seed particles 35. This additional liquid droplet quickly coats the surface of the seed particle and dries, adding an extra layer of thickness to the seed particle. Over a period of time, more and more droplets adsorb onto the surface of the fluidized particle, forming a layered onion-like particle 36. FIG. 3 shows a cross-section of a fully formed particle 36 showing the layered structure.

[0065] Once the particles reach a pre-determined particle size, they are recovered from the spray granulator. The particles are then preferably heat treated to remove any remaining binder from the particles and to provide a degree of mechanical stability. Heat treatment may also result in the particles being homogenous in composition. Thus, the recovered particles 36 may be subjected to a heat treatment process. The heat treatment may be, for example, a two-step process including heating to 500° C. and holding for a period of time, followed by heating to 1000° C. and holding for a further period of time.

[0066] After the particles have been recovered and heat treated if necessary, the feed powder may be reduced to form a metal. Preferably, the feed powder is directly reduced in powder form to produce a metal powder. However, it may be desirable to form the feed powder into a preform shape or pellets prior to reduction to a metal.

[0067] 9 illustrates an electrolysis apparatus 110 configured for use in carrying out the reduction of a feedstock powder. The apparatus includes a stainless steel cathode 120 and a carbon anode 130 located within an electrolysis cell housing 140. The anode 130 is disposed above and spatially separated from the cathode 120. In one particular embodiment, the housing 140 may contain 500 kg of a calcium chloride-based molten salt electrolyte 150, which may be CaCl 2and 0.4 wt. % CaO. Both the anode 130 and the cathode 120 are disposed in contact with the molten salt 150. Both the anode 130 and the cathode 120 are connected to a power source 160, which allows an electrical potential to be applied between the cathode and the anode.

[0068] Both cathode 120 and anode 130 are oriented substantially horizontally, with the top surface of cathode 120 facing the bottom surface of anode 130 .

[0069] The cathode 120 includes a rim 170 that extends upwardly from the periphery of the cathode and acts as a retention barrier for the feedstock powder 190 supported on the upper surface of the cathode. The rim 170 is integral with the cathode and is formed from the same material as the cathode. In other embodiments, the rim may be formed from a different material than the cathode, for example an electrically insulating material.

[0070] The structure of the cathode can be seen in more detail in Figures 10 and 11. The rim 170 is in the form of a ring with a diameter of 30 cm. A first supporting cross member 175 extends across the diameter of the rim. The cathode also comprises a mesh support member 171, which is in the form of a ring having the same diameter as the rim 170. The mesh support member has a second supporting cross member 176 of the same dimensions as the supporting cross member 175 on the rim 170. A mesh 180 is supported by being sandwiched between the rim 170 and the mesh support member 171 (mesh 180 is shown as a dotted line in Figure 10). The mesh 180 comprises a stainless steel cloth of mesh size 100, which is held taut by the rim 170 and the mesh support member. The cross member 175 is placed against the bottom surface of the mesh 180 and serves to support the mesh. The top surface of the mesh 180 serves as the top surface of the cathode.

[0071] The stainless steel cloth forming the mesh 180 is made from 30 micrometer thick 304 grade stainless steel wires that are woven to form a cloth with square holes of 150 micrometer openings. The mesh size can vary and should generally be of a smaller diameter than the average particle size of the feedstock powder to be reduced. The mesh 180, cross member 175, and rim 170 that form the cathode are all electrically conductive. In other embodiments, the mesh may be the only conductive element of the cathode.

[0072] In use, the feed powder 190 can be reduced by applying a potential between the cathode 120 and the anode 130 sufficient to remove oxygen from the feed powder. The metal powder product remaining after reduction can be removed and washed to separate the metal powder from residual salts. EXAMPLES

[0073] As a specific example, Ti-Al-V alloys were formed using various embodiments of the invention disclosed herein. The initial starting oxide powders used to form the feed powder for reduction were TiO2, Al2O3, and V2O5. The TiO2 oxide powder had an average particle size of 1.2 microns. The Al2O3 oxide powder had an average particle size of 8.2 micrometers. The V2O5 powder had an average particle size of 97.7 micrometers. Mixing these three oxide powders in the appropriate ratios to form an alloy containing low percentages of Al and V, such as Ti-6Al-4V alloy powder, is extremely difficult due to the large disparity between the initial particle sizes of the starting oxides. Although large pellets with the desired ratios of oxides may be formed, it is clear that they are unlikely to approximate the narrow range of composition required to form Ti-6Al-4V alloy.

[0074] A total of 4800 grams of mixed oxide powder was used. Of the 4800 grams, 4195 grams were TiO2, 402 grams were Al2O3, and 203 grams were V2O5. This corresponds to the metallic elemental proportions of 88.5% Ti, 7.5% Al, and 4% V. This feedstock was produced as an initial proof of concept. It was expected that an oxide feedstock powder of this composition, upon reduction by the FFC process, would produce an alloy with a composition approximating Ti-6Al-4V. It should be noted that the percentage of aluminum in the feedstock powder was intentionally increased above 6% to account for aluminum loss during the reduction process.

[0075] The oxide powder was mixed with a liquid to form a slurry with 59.5% solid oxide. The liquid consisted of an aqueous solution of demineralized water and PVA. The percentage of PVA was dependent on the total oxide loading. Thus, the percentage of PVA was 2.5% by weight of the total oxide loading. The liquid mixture was then subjected to high shear mixing for 15 minutes at a rotation speed of 6500 rpm. The shear mixing was carried out using an IKA Dispersion Mixer Model G45M.

[0076] After shear mixing, the liquid and oxide mixture formed a suspension of ground oxide particles in the liquid / binder. The oxide particle size was substantially homogenous and the oxide particles in the suspension had a diameter of about 2 micrometers or less. This suspension was then subjected to a fluidized bed spray granulation process to produce solid oxide particles. A Glatt Procell Labsystem spray granulator was used to form the metal oxide particles. A fluidizing airflow through the apparatus was 150 m 3 The process parameters were set at a flow rate of 100 g / h and an air temperature of 120° C. The suspension was sprayed into the chamber at an atomization pressure of 3 bar and a spray rate of 57 g / min. These parameters were selected to result in an average product particle size in the range of 100-200 micrometers.

[0077] After spray granulation, the recovered oxide particles were heat treated. The heat treatment was carried out to remove the organic components of the PVA binder and to impart mechanical strength to the individual powder particles. This heat treatment schedule also homogenized the composition of each particle forming a solid solution of the metal oxide mixture.

[0078] To heat treat the oxide particles produced by spray granulation, they were heated in an electrically heated furnace at a rate of 3°C / min to a temperature of 550°C. The particles were kept at this temperature for 1 hour to remove traces of organic binder. The particles were then heated at 3°C / min to 1000°C and held at that temperature for an additional 2 hours before being cooled to room temperature. The resulting feed powder is shown in Figure 4.

[0079] FIG. 4 shows a feed powder for reduction to form a Ti-Al-V powder. The feed powder was analyzed using a Malvern Mastersizer 2000 and found to contain a plurality of feed particles having an average particle size of about 160 micrometers. The D10 particle size is 119 micrometers and the D90 particle size is 225 micrometers. The feed powder is substantially spherical and has a mixed oxide composition including titanium, aluminum, and vanadium.

[0080] A portion of the feed powder was sampled and polished. Figure 5 shows an SEM micrograph of the powder. It can be seen that the powder particles are substantially uniform in size and relatively porous. The porosity of the powder can facilitate reduction of the powder using a molten salt reduction process.

[0081] The distribution of aluminum, vanadium, and titanium was analyzed using X-ray elemental mapping in a scanning electron microscope (SEM). Figure 6 shows the distribution of aluminum in the sample of Figure 5, Figure 7 shows the distribution of vanadium in the same sample, and Figure 8 shows the distribution of titanium in the same sample. Although the distribution of aluminum in Figure 6 is not clear, possibly due to the low atomic weight of aluminum, it can be seen that the distribution of vanadium and titanium in the particles appears homogenous; that is, there are no vanadium-rich or vanadium-deficient areas in the particles shown in Figure 5. Considering that the initial vanadium particle size was approximately 100 micrometers, it can be seen that the high shear mixing step followed by the spray granulation step produced homogenous feed powder particles with the desired elemental distribution, with an average particle size of about 160 micrometers.

[0082] The feed powder was reduced to a metal alloy powder using an apparatus of the type described above in connection with Figure 9. Approximately 20 grams of the feed powder was placed on top of the cathode 20 in contact with the molten salt 150. The feed powder 190 was supported on the mesh 180 of the cathode. The depth of the feed powder 190 was approximately 1 centimeter.

[0083] Molten salt 50 (CaCl2 and 0.4 wt.% CaO) was maintained at a temperature of 950°C and a potential was applied between the anode and cathode. Heat flow and gas lift deflection caused by the buoyancy of gases evolved at the anode (mainly CO and CO2) circulate the molten salt through the cell, creating a flow of the molten salt through the bed of feed powder. The cell was operated in constant current mode with a current of 5 amps for 16 hours. After this time the cell was cooled and the cathode was removed and cleaned to remove salt from the reduced feed powder.

[0084] The reduced feedstock powder was removed from the cathode as a friable mass of metal alloy powder particles. The mass was crushed with an agate pestle and mortar to separate the material into individual powder particles. The particles were then dried and analyzed. Analysis revealed that the powder particles were a homogenous titanium alloy having an approximate composition of Ti-6Al-6V. FIG. 12 is an SEM micrograph of one of the metal powder particles. This initial attempt shows that common commercial alloys, such as Ti-6Al-4V or Ti-6Al-6V-2Sn, can be produced using embodiments of the present invention by varying the oxide ratio or oxide species used to form the feedstock. EXAMPLES

[0085] As a further example, titanium-aluminide intermetallic compounds (Ti-Al-Nb-Cr intermetallic compounds) were formed using various embodiments of the invention disclosed herein. The initial starting oxide powders used to form the feed powder for reduction were TiO2, Al2O3, Nb2O5, and Cr2O3. The TiO2 oxide powder had an average particle size of 1.2 microns. The Al2O3 oxide powder had an average particle size of 8.2 micrometers. The Nb2O5 powder had an average particle size of 0.5-2 micrometers, and the Cr2O3 powder had an average particle size of 1-5 micrometers.

[0086] A total of 5000 grams of mixed oxide powder was used, of which 2861.4 grams was TiO2, 1826.7 grams was Al2O3, 198.4 grams was Nb2O5, and 113.5 grams was Cr2O3.

[0087] The oxide powder was mixed with an aqueous solution of demineralized water and PVA to form a slurry having 59.5% solid oxide. This slurry was then subjected to high shear mixing and spray granulation as described in connection with Example 1. The spray granulation parameters were selected to result in a particle size distribution in the range of 100-250 micrometers. The product of the spray granulation was a grey-green granular free-flowing powder.

[0088] After spray granulation, the recovered oxide particles were heat treated to form a feed powder as described above in connection with Example 1. The feed powder was then reduced using the reduction process described in connection with Example 1. The reduced powder was then recovered and washed. SEM-EDX analysis of some of the powder particles revealed that the metal alloy powder had an average composition of Al 45.46 atomic %, Ti 50.23 atomic %, Cr 2.09 atomic %, Nb 2.22 atomic %. EXAMPLES

[0089] As a further example, titanium-tantalum alloys (Ti-Ta alloys) were formed using various embodiments of the invention disclosed herein. The initial starting oxide powders used to form the feed powder for reduction were TiO2 and Ta2O5. The TiO2 oxide powder had an average particle size of 1.2 microns. The Ta2O5 oxide powder aggregates had an average particle size of 300 micrometers.

[0090] A total of 5000 grams of mixed oxide powder was used, of which 3806.3 grams was TiO2 and 1193.7 grams was Ta2O5.

[0091] The oxide powder was mixed with an aqueous solution of demineralized water and PVA to form a slurry having 53.2% solid oxide. This slurry was then subjected to high shear mixing and spray granulation as described in connection with Example 1. The spray granulation parameters were selected to result in a particle size distribution in the range of 100-250 micrometers. The product of the spray granulation was a grey-green granular free-flowing powder.

[0092] After spray granulation, the recovered oxide particles were heat treated to form a feed powder as described above in connection with Example 1. The feed powder was then reduced using the reduction process described in connection with Example 1. The reduced powder was then recovered and washed. SEM-EDX analysis of some of the powder particles revealed that the metal alloy powder had an average composition of 70.19 wt.% Ti and 29.81 wt.% Ta. EXAMPLES

[0093] As a further example, various embodiments of the invention disclosed herein were used to form a tantalum-tungsten alloy (Ta-W alloy). The initial starting oxide powders used to form the feedstock powder for reduction were Ta2O5 and W2O3. The Ta2O5 oxide powder aggregates had an average particle size of 300 micrometers. The WO3 oxide powder had a particle size distribution of 0.5-5 micrometers.

[0094] A total of 5000 grams of mixed oxide powder was used, of which 4871 grams was Ta2O5 and 129 grams was WO3.

[0095] The oxide powder was mixed with an aqueous solution of demineralized water and PVA to form a slurry having 59.5% solid oxide. This slurry was then subjected to high shear mixing and spray granulation as described in connection with Example 1. The spray granulation parameters were selected to result in a particle size distribution in the range of 100-250 micrometers. The product of the spray granulation was a grey-green granular free-flowing powder.

[0096] After spray granulation, the recovered oxide particles were heat treated to form a feed powder as described above in connection with Example 1. The feed powder was then reduced using the reduction process described in connection with Example 1. The reduced powder was then recovered and washed. SEM-EDX analysis of some of the powder particles revealed that the metal alloy powder had an average composition of 93.61 wt.% Ta and 6.39 wt.% W. EXAMPLES

[0097] As a further example, tantalum-aluminum alloys (Ta-Al alloys) were formed using various embodiments of the invention disclosed herein. The initial starting oxide powders used to form the feedstock powder for reduction were Ta2O5 and Al2O3. The Ta2O5 oxide powder aggregates had an average particle size of 300 micrometers. The Al2O3 oxide powder aggregates had an average particle size of 120 micrometers.

[0098] A total of 5000 grams of mixed oxide powder was used, of which 4847 grams was Ta2O5 and 153 grams was Al2O3.

[0099] The oxide powder was mixed with an aqueous solution of demineralized water and PVA to form a slurry having 59.5% solid oxide. This slurry was then subjected to high shear mixing and spray granulation as described in connection with Example 1. The spray granulation parameters were selected to result in a particle size distribution in the range of 100-250 micrometers. The product of the spray granulation was a grey-green granular free-flowing powder.

[0100] After spray granulation, the recovered oxide particles were heat treated to form a feed powder as described above in connection with Example 1. The feed powder was then reduced using the reduction process described in connection with Example 1. The reduced powder was then recovered and washed. SEM-EDX analysis of some of the powder particles revealed that the metal alloy powder had an average composition of 97.84 wt.% Ta and 2.16 wt.% Al.

Claims

1. 1. A method for producing a non-metallic feedstock powder suitable for reduction to a metal alloy, comprising the steps of: combining a liquid with solid metal oxide particles to form a mixture, wherein the sum of all metal oxide particles combined with the liquid to form the mixture comprises between 50% and 70% by weight of the mixture; subjecting the mixture to high shear mixing to form a suspension of metal oxide and the liquid; drying the suspension using a fluid bed spray granulation process to grow a plurality of particles and form the non-metallic feedstock powder; The method includes:

2. Drying the suspension comprises: spraying a portion of the suspension into a heated chamber of a fluid bed spray granulator, thereby removing liquid from individual droplets of the suspension to form a plurality of seed particles; maintaining the plurality of seed particles within the heating chamber with a fluidizing gas flow; spraying a further portion of the suspension into the heating chamber such that droplets of the suspension successively adhere to the plurality of seed particles and dry, thereby growing the particles to form the non-metallic feedstock powder; The method of claim 1 , comprising:

3. The method of claim 1 or claim 2, wherein the liquid comprises water and an organic binder.

4. 4. The method of claim 1, wherein a first set of metal oxide particles and a second set of metal oxide particles are combined with the liquid to form the mixture, and the first set of metal oxide particles and the second set of metal oxide particles have an average particle size difference of more than a factor of two.

5. The method of claim 4 comprising three or more sets of metal oxide particles, each of the three or more sets having a different composition.

6. 6. The method of claim 1, wherein the process of forming the non-metallic feedstock powder is controlled such that the non-metallic feedstock powder has a predetermined average particle size between 10 micrometers and 10 millimeters.

7. 7. The method of any one of claims 1 to 6, wherein the process of forming the non-metallic feedstock powder is controlled such that the non-metallic feedstock powder has a particle size distribution between a D10 diameter and a D90 diameter of less than 100 micrometers.

8. 8. The method of any one of claims 1 to 7, wherein the high shear mixing is carried out using a rotor rotating at more than 5000 rpm.

9. 9. The method of claim 1, wherein the process of forming the non-metallic feedstock powder comprises heat treating the plurality of particles to impart mechanical strength and / or chemical homogeneity to each particle.

10. 10. A non-metallic feedstock powder formed by the method of any one of claims 1 to 9.

11. Suitable for reduction to a Ti-Al-V alloy, comprising titanium, aluminum, vanadium, and oxygen; or Suitable for reduction to a Ti-Al-Nb-Cr alloy, comprising titanium, aluminum, chromium, niobium, and oxygen; or containing titanium, tantalum, and oxygen, suitable for reduction to a Ti-Ta alloy; or containing tantalum, aluminum, and oxygen, suitable for reduction to a Ta—Al alloy; or a Ta—W alloy containing tantalum, tungsten, and oxygen, suitable for reduction to a Ta—W alloy; 11. The non-metallic feedstock powder of claim 10.

12. Forming a non-metallic feedstock using a method according to any one of claims 1 to 11; reducing the non-metallic feedstock powder to form a metal alloy; A method for producing a metal alloy comprising:

13. 13. The method of claim 12, wherein the reduction of the non-metallic feedstock powder is carried out by electrolytic reduction of the non-metallic feedstock powder in contact with a molten salt.

14. the metal alloy produced is a titanium-aluminium-vanadium alloy, and particles of titanium oxide, aluminium oxide and vanadium oxide are mixed with the liquid to form the mixture; or the metal alloy being produced is a titanium-aluminum-niobium-chromium intermetallic compound, and particles of titanium oxide, aluminum oxide, niobium oxide, and chromium oxide are mixed with the liquid to form the mixture; or the metal alloy produced is a titanium-tantalum alloy, and particles of titanium oxide and tantalum oxide are mixed with the liquid to form the mixture; or the metal alloy produced is a tantalum-tungsten alloy, and tantalum oxide and tungsten oxide particles are mixed with the liquid to form the mixture; or the metal alloy produced is a tantalum-aluminum alloy, and particles of tantalum oxide and aluminum oxide are mixed with the liquid to form the mixture; The method according to claim 12 or claim 13.

15. A metal alloy formed by the method of any one of claims 12 to 14.

Citation Information

Patent Citations

  • Method for producing hard metal granules

    JP2004518825A

  • Method for producing silver-based powder composites for electrical contact materials and powder composites produced thereby

    JP2009531539A

  • Manufacture of metal alloy powder

    JP2009544840A

  • Electrolytic manufacturing of powders

    JP2014531517A

  • Zinc titanate sorbents

    US5714431A